Registration of 'Dayn' Hard White Spring Wheat. Issue 2 (12th April 2018) - Kidwell, K. K.; Kuehner, J. S.; Shelton, G. B.; DeMacon, V. L.; Rynearson, S.; Chen, X. M.; Guy, S. O.; Marshall, J. M.; Engle, D. A.; See, D. R.; Morris, C. F.; Pumphrey, M. O.
Abstract : Hard white spring wheat ( Triticum aestivum L.) production in the western United States is concentrated in regions of California, southern Idaho, and Washington, where resistance to stripe rust, high yield potential, minimal lodging, and desirable milling and baking qualities are preferred traits. Our objective was to develop a broadly adapted hard white spring wheat cultivar with a high level of resistance to stripe rust. 'Dayn' (Reg. No. CV‐1138, PI 666941) hard white spring wheat was developed by the Washington State University Agricultural Research Center and released for production in the Pacific Northwest. Dayn was derived from the cross 'UI Lochsa'//'Otis'*2/P9347A1‐2 by a modified‐pedigree bulk‐breeding method. Dayn was tested at sites across Washington and Idaho under the designations WA8123 and Dayn from 2010 to 2016. Dayn is a medium‐maturity, semidwarf cultivar broadly adapted to spring wheat production areas of the Pacific Northwest, with excellent yield potential in high‐moisture rainfed and irrigated production systems. Dayn was released on the basis of a combination of superior grain yield potential compared with contemporary commercial cultivars, a high level of resistance to stripe rust, and desirable milling and baking characteristics.